Influence of Angles of Attack, Frequency and Kick Amplitude on Swimmer`s Horizontal Velocity During Underwater Phase of a Grab Start - Houel, N.; Elipot, M.; André, F.; Hellard, P. (Journal of Applied Biomechanics, 2013)
The underwater phase of starts represents an important part of the performance in sprint swimming`s events. Kinematics variables that swimmers have to take into account to improve their underwater phase of starts are unknown. The aim of this study was to determine the kinematics variables that improve performance during the underwater phase of grab starts. A three-dimensional analysis of the underwater phase of ten swimmers of national level was conducted. Stepwise multiple linear regressions identified the main kinematics variables that influence the horizontal velocity of the swimmer each 0.5 m in the range of 5 to 7.5 m. The results show that the kinematics parameters change during the range of 5 to 7.5 m of the underwater phase of the starts. For this population of swimmers, the results enable proposals of four principles to improve the underwater phase: i) to be streamlined at the beginning of the underwater gliding phase, ii) to start the dolphin kicking after 6 m, iii) to generate propulsive forces using only feet and legs during underwater undulatory swimming, iv) to improve the frequency of underwater undulatory swimming.